An Analysis of the Role of Law in Women Empowerment in Pakistan (2001-2018) - Sultan, Akmal; Ali, Najaf; Ashraf, Muhammad Javed (Annals of Human and Social Sciences, 2025)
This research article investigates the complicated landscape of woman empowerment in Pakistan, focusing on the legal aspects that have shaped its route from 2001 to 2018. Through an analysis of the legal frameworks over legislation and policy and their actual impact, the study seeks to identify the ways in which laws have helped to improve women's position and power in society. Covering a period of significant sociopolitical shifts, the article reflects on important legislative developments through a discussion of several amendments to the Pakistan Penal Code and the Family Laws Ordinance to curb gender-based violence and discriminatory practices. It also explores how recognition of the Women's Protection Act of 2006 and the creation of gender-sensitive forums, including family courts and women's crisis centers assist women in accessing justice. Based on a literature and official documents the article provides important insights into Pakistani women empowerment in its current and changing dynamics.